Correlation of DEFA1 Gene Copy Number Variation with Intestinal Involvement in Behcet's Disease - Ahn, Joong Kyong (The Korean Academy of Medical Sciences, 2012)
Copy number variation has been associated with various autoimmune diseases. We investigated the copy number (CN) of the DEFA1 gene encoding α-defensin-1 in samples from Korean individuals with Behcet's disease (BD) compared to healthy controls (HC). We recruited 55 BD patients and 35 HC. A duplex Taqman® real-time PCR assay was used to assess CN. Most samples (31.1%) had a CN of 5 with a mean CN of 5.4 ± 0.2. There was no significant difference in the CN of the DEFA1 gene between BD patients and HC. A high DEFA1 gene CN was significantly associated with intestinal involvement in BD patients. Variable DEFA1 gene CNs were observed in both BD patients and HC and a high DEFA1 gene CN may be associated with susceptibility to intestinal involvement in BD.